2010
DOI: 10.1038/onc.2010.21
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 is a direct transcriptional target of GATA3 in neuroblastoma tumor cells

Abstract: Almost all neuroblastoma tumors express excess levels of Cyclin D1 (CCND1) compared to normal tissues and other tumor types. Only a small percentage of these neuroblastoma tumors have high-level amplification of the Cyclin D1 gene. The other neuroblastoma tumors have equally high Cyclin D1 expression without amplification. Silencing of Cyclin D1 expression was previously found to trigger differentiation of neuroblastoma cells. Overexpression of Cyclin D1 is therefore one of the most frequent mechanisms with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…In luminal progenitor cells, Gata3 was shown to directly bind to the promoter and intron of Cdkn2c and repress its expression to regulate the cell cycle (19). In addition, the involvement of Gata3 in the activation of Cyclin D1 (encoded by Ccnd1) in neuroblastoma cell lines and cell cycle entry in long-term repopulating hematopoietic stem cells were reported in previous studies (21,29). Therefore, Gata3 appears to regulate the proliferation of various cell types through several distinct mechanisms.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In luminal progenitor cells, Gata3 was shown to directly bind to the promoter and intron of Cdkn2c and repress its expression to regulate the cell cycle (19). In addition, the involvement of Gata3 in the activation of Cyclin D1 (encoded by Ccnd1) in neuroblastoma cell lines and cell cycle entry in long-term repopulating hematopoietic stem cells were reported in previous studies (21,29). Therefore, Gata3 appears to regulate the proliferation of various cell types through several distinct mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier reports demonstrated that Gata3 regulates cell cycle in luminal progenitor cells and neuroblastoma cell via control of Cdkn2c and Ccnd1 expression, respectively (19,21). Thus, we next assessed the expression of Cdkn2c and Ccnd1 in primary Th1 and Th2 cells from wild-type or Gata3-deficient mice.…”
Section: Identification Of Ruvbl2 As a Molecule That Interacts With Gmentioning
confidence: 99%
“…85 GATA2, GATA3, GATA4, and FOG2 are expressed in human neuroblastoma, with overexpression of GATA4 correlating with less favorable subtypes and overexpression of GATA2, GATA3, and FOG2 with more favorable subtypes. 86 In neuroblastoma cell lines, GATA3 was found to positively regulate cyclin D1, which maintains cells in an undifferentiated state, 87,88 suggesting that GATA3 has oncogenic potential in neuroblastoma.…”
Section: Monographsmentioning
confidence: 98%
“…33 In addition, cyclin D1 whose levels in the majority of neuroblastomas were much higher than those in normal tissues or other types of tumors was directly upregulated by GATA3. 35 A recent study showed that, even in breast cancer in which GATA3 loss correlated with tumor progression, GATA3 silencing resulted in inhibition of cell proliferation and facilitation of G 1 -to S-phase transition through transcriptional regulation of cyclin D1. 36 Together with the data in the current study and other findings in breast cancer, the functions of GATA3 and its downstream targets are likely cancer type-specific or possibly cell line-specific.…”
Section: Discussionmentioning
confidence: 99%